SEMIOTIC ANALYSIS OF THE CAT FOOD “WHISKAS” ADVERTISEMENT - Devi Damaiyanti; Dewanto Dewanto; Ari Astutik (EL2J (English Language and Literature Journal), 2023)
This article is entitled “THE ANALYSIS SEMOTIC OF WHISKAS AN ADVERTISEMENT CAT FOOD” advertising is communication with the specific purpose of commerce a product or service. Semiotics is the science of signs. This research has the purpose of analysis semiotic in advertisement Whiskas. The analysis research meaning in semiotics and focuses more on and understands a sign and a sign when the sign is advertised Whiskas is a cat food brand that Whiskas has been producing the best cat food since 1958 and we always improve and guarantee the quality and quality of the best nutritional cat food throughout history. This research used the theory Ferdinand de Saussure system signifier and signified. The method employed in this analysis is descriptive qualitative with this Associate in there's an understanding of semiotics in advertisement Whiskas cat food. In the research analysis two questions are signs on advertisement Whiskas and characteristics of advertisement Whiskas. the data analysis takes in the website and YouTube.